2019
DOI: 10.1155/2019/8192439
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Extracted from Cymbopogon citronella Leaves by Supercritical Carbon Dioxide: Antioxidant and Antimicrobial Activities

Abstract: To improve essential oil quality, especially to reserve the thermal instability of compounds, supercritical CO2 extraction (SFE) was applied to recover essential oil from Cymbopogon citronella leaves. A response surface methodology was applied to optimize the extraction process. The highest essential oil yield was predicted at extraction time 120  min, extraction pressure 25  MPa, extraction temperature 35°C, and CO2 flow 18  L/h for the SFE processing. Under these experimental conditions, the mean essential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 24 publications
0
15
0
5
Order By: Relevance
“…Wu et al have shown that high doses of substances known to have antioxidant property tend to have pro-oxidant activities. 26 In order to further investigate the apoptotic pathways LG may utilize to induce apoptosis, we conducted experiments to see whether inhibition of certain pathways would reduce cell death with the respective treatments. Interestingly, the addition of n-acetyl cysteine (NAC; an antioxidant agent) and Z-VAD-FMK (an irreversible pan-caspase inhibitor) did not inhibit apoptosis in LG-treated cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al have shown that high doses of substances known to have antioxidant property tend to have pro-oxidant activities. 26 In order to further investigate the apoptotic pathways LG may utilize to induce apoptosis, we conducted experiments to see whether inhibition of certain pathways would reduce cell death with the respective treatments. Interestingly, the addition of n-acetyl cysteine (NAC; an antioxidant agent) and Z-VAD-FMK (an irreversible pan-caspase inhibitor) did not inhibit apoptosis in LG-treated cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Lemongrass essential oil may be extracted by many different methods like solvent extraction, steam distillation, hydrodistillation (HD), microwave-assisted hydrodistillation (MAHD), and supercritical uid extraction (SFE) with CO 2 . A number of studies have proved that the quality of essential oils depends mainly on its constituents, which is signi cantly in uenced by the extraction techniques [Desai & Parikh, 2015;Schaneberg & Khan, 2002;Wu et al, 2019]. Moreover, methods involving heating may induce thermal degradation or hydrolysis of fragile constituents.…”
Section: Extraction Of Lemongrass Essential Oilmentioning
confidence: 99%
“…Studies have shown that the main commercial repellents are related to the repellency by the olfactory system of Ae. aegypti , such as DEET, [29] Icaridin, [12] and Citronellol Oil [30] …”
Section: Resultsmentioning
confidence: 99%